Catalytic Performance of Environmentally Friendly Calcium Sulfate Hemihydrate-supported Metals (Ti, Fe, Cu or Ag) for Oxidation Styrene to Benzaldehyde - Agung Rahmadani; Mukhamad Nurhadi; Teguh Wirawan; Wirhanuddin Wirhanuddin; Nabila Nur Agusti; Sin Yuan Lai; Hadi Nur (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
This paper presents the synthesis and characterization of calcium sulfate hemihydrate (CSH)-supported Metals (Ti, Fe, Cu or Ag) catalysts and their application in the styrene oxidation to benzaldehyde using hydrogen peroxide (H2O2) as an oxidant. The study explores the catalyst's structure-activity relationship, emphasizing the importance of mesoporous materials for enhanced catalytic performance. The CSH-Metals catalysts were synthesized using fish bone-derived CSH as a support, which aligns with green chemistry principles. Characterization techniques, such as FTIR, XRD, SEM, and BET surface area analysis, confirmed the successful impregnation of Metals (Ti, Fe, Cu or Ag) and its catalytic performance. The catalysts exhibited styrene conversion and high selectivity for benzaldehyde, achieving up to 49.5% and 60.2% for CSH-Ti; 12.9% and 84.1% for CSH-Fe, 19.9% and 61.5% for CSH-Cu, and 13.4% and 92.8% for CSH-Ag. The research highlights that the best catalyst’s performance are CSH-Ti for styrene conversion and CSH-Ag for benzaldehyde selectivity. To support performance interpretation, a fuzzy logic analysis was applied to evaluate the influence of seven key parameters on catalytic behavior. The results revealed that ROS (Reactive Oxygen Species) formation activity, type of metal, and metal–intermediate interaction were the most dominant factors affecting performance. This data-driven insight reinforces the chemical reactivity as the primary determinant of catalyst effectiveness, above physical attributes such as surface area or pore structure. Overall, this study introduces a cost-effective, sustainable, and selective catalyst system for styrene oxidation, demonstrating high potential for industrial application in the production of value-added chemicals with minimal environmental impact. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).